2013
DOI: 10.1002/btpr.1784
|View full text |Cite
|
Sign up to set email alerts
|

Active, soluble recombinant melittin purified by extracting insoluble lysate of Escherichia coli without denaturation

Abstract: Cell lytic peptides are a class of drugs that can be used to selectively kill invading organisms or diseased cells. Several of these peptides have been identified as potential therapeutics. Herein, we report a novel process for purifying recombinant melittin, a cell lytic peptide that inserts into the membranes of cells causing cell lysis, from Escherichia coli. The process involves surfactant and low pH to solubilize melittin fusion proteins from the insoluble fraction of bacterial lysates. We are able to sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…It has been shown that melittin, in its native form, at concentrations under 3 μM has anti-inflammatory properties, but validation of the toxicity at these concentrations toward the cell-lines was not apparent (Mosser and Edwards, 2008; Park et al, 2004; Park et al, 2007). We have observed that melittin, in its native form, has toxicity at concentrations in the nanomolar range in macrophages having previously shown similar toxicity in bacteria and cancer lines (Buhrman et al, 2013a; Buhrman et al, 2013b; Buhrman et al, 2013c; Buhrman et al, 2012). This is consistent with several studies in other cell types (Nah et al, 2007; Nishikawa and Kitani, 2011; Soman et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…It has been shown that melittin, in its native form, at concentrations under 3 μM has anti-inflammatory properties, but validation of the toxicity at these concentrations toward the cell-lines was not apparent (Mosser and Edwards, 2008; Park et al, 2004; Park et al, 2007). We have observed that melittin, in its native form, has toxicity at concentrations in the nanomolar range in macrophages having previously shown similar toxicity in bacteria and cancer lines (Buhrman et al, 2013a; Buhrman et al, 2013b; Buhrman et al, 2013c; Buhrman et al, 2012). This is consistent with several studies in other cell types (Nah et al, 2007; Nishikawa and Kitani, 2011; Soman et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
“…After cleavage of the GST from the melittin via a thrombin-cleavable site (Buhrman et al, 2013b; Buhrman et al, 2013c), we show decreases in cellular viability, interpreted as cell death, similar to the native peptide at these concentrations ( Figure 1C ). Similarly, we show that native peptide with the addition of free GST maintains ability to kill ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations